Correlations between college students’ perception and goal of body weight, and their consumption behaviors of sugar-sweetened beverages and fried potatoes - Mardiyati, Nur (Kansas State University, 2015)
The number of overweight and obese college students in the United States has remained high, which could be related to the comfort food and beverages consumed. Sugar-sweetened beverages and fried potatoes are beverages and comfort food commonly consumed by college students. Furthermore, people’s behavior is affected by their perceptions and goals. Thus, this study aimed to assess the correlations between the perception, goal of body weight, and sugar-sweetened beverages and fried potatoes consumption behaviours of college students. A cross-sectional survey of 371 college students was conducted via a self-reporting questionnaire that included information related to sugar-sweetened beverages and fried potato consumption behavior in the past month. The involved students also described their body weight perception and future goal. Spearman correlation and Chi-square analyses were performed to examine the associations. There were significant associations (p<0.0001) between perception of body weight and goal of body weight, regular soda consumption and other sweetened beverage consumption, regular soda consumption and fried potato consumption, and other sweetened beverage consumption and fried potatoes consumption. In addition, there were significant correlations between goals of body weight and other sweetened beverage consumption (p=0.0370). These findings confirmed that perception of body weight was associated with goal of body weight and provided a significant importance for educational intervention to students on improving awareness of healthy body weight and eating.
Keywords: Comfort food; Body weight perception; Body weight goals; Sugar-sweetened beverages; College students; Behavioral Sciences (0602); Nutrition (0570)